Relevance of public active participation to address the complexity of science-based issues, such as biodiversity loss - Ficorilli, Antonella; Rufo, Fabrizio (Annali di Botanica, 2024)
In the light of the increasingly prominent role played by science in public life, the definition of a space for public participation is a key issue in the current relationship between science and society. This is especially true when science-based issues, which are often ethically sensitive and controversial, are at stake, such as environmental issues. The paper suggests the usefulness of an active role of the public together with researchers and policymakers in both the decision-making process and the activities to be carried out to address the complexity of current science-based issues, with a focus on the anthropogenic loss of biodiversity and the demand for its conservation and restoration.